3-Azidothieno[2,3-b]pyridine Thermolysis as a Route to Novel peri-Annelated Heterocyclic Derivatives – Benzo(furo)thieno[2,3,4-ij]-2,7-naphthyridines - Vasilin, Vladimir K.; Kanishcheva, Eugeniya A.; Stroganova, Tatyana A.; Krapivin, Gennady D. (Synlett, 2015)
Synthesis of novel benzo(furo)thieno[2,3,4-ij]-2,7-naphthyridines based on alkyl(aryl) 3-azido-4-aryl(furyl)thieno[2,3-b]pyridine-2-carboxylate thermolysis is elaborated. The structures of the synthesized materials were assigned by their NMR, IR, and MS analysis.
Keywords: thieno[2,3-b]pyridine; azides; fused-ring systems; thermolysis; nitrene; cyclization; naphthyridine